Delivering the Goods Building Local Government Capacity to Achieve the Millennium Development Goals - United Nations Capital Development Fund (United Nations Capital Development Fund, 2005)
This Practitionerâ€™s Guide has been long in the making â€“ longer even than the 22 month gestation period enjoyed by elephants. But I believe that it has been worth it. It is an important publication for several reasons. Firstly, and more parochially, UNCDF is an organization which has always prided itself on its internal learning and policy-development processes. We therefore attach a great deal of importance to this kind of attempt to capture and â€œcodifyâ€ the various sorts of lessons which are emerging from our growing portfolio of Local Development Programmes â€“ which are now active in some 25 Least Developed Countries. In doing so it also provides a common language or framework (a set of organizing â€œboxesâ€) which can be used to continually update and further enrich the lesson-learning process in the future.